2012
DOI: 10.1007/s00894-012-1651-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying the 1–4 intramolecular scaling factor in atomistic simulations of long-chain N-alkanes with the OPLS-AA model

Abstract: A comprehensive molecular dynamics simulation study of n-alkanes using the optimized potential for liquid simulation with all-atoms (OPLS-AA) force field at ambient condition has been performed. Our results indicate that while simulations with the OPLS-AA force field accurately predict the liquid state mass density for n-alkanes with carbon number equal or less than 10, for n-alkanes with carbon number equal or exceeding 12, the OPLS-AA force field with the standard scaling factor for the 1-4 intramolecular Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
8
32
0
Order By: Relevance
“…The initial parameterizations of the popular all-atom force-fields OPLS-AA and AMBER-AA over-predicted the density by 14% and 11%, respectively, at ambient conditions. This density over-prediction has been observed in previous simulations of long chain alkanes using these force-fields at ambient conditions and has been attributed to crystallization due to the over-prediction of the melting point (Figure 1a) [16,17,20]. Crystallization did not occur at 423 K and 60.8 MPa, and both OPLS-AA and AMBER-AA under-predicted the density by around 4%.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The initial parameterizations of the popular all-atom force-fields OPLS-AA and AMBER-AA over-predicted the density by 14% and 11%, respectively, at ambient conditions. This density over-prediction has been observed in previous simulations of long chain alkanes using these force-fields at ambient conditions and has been attributed to crystallization due to the over-prediction of the melting point (Figure 1a) [16,17,20]. Crystallization did not occur at 423 K and 60.8 MPa, and both OPLS-AA and AMBER-AA under-predicted the density by around 4%.…”
Section: Resultssupporting
confidence: 61%
“…Although improvements to the prediction of transport properties by united-atom force-fields have been made by using modified forms of non-bonded interaction (other than Lennard-Jones), such changes can often have a detrimental effect on the thermodynamic properties for which the force-fields were originally parameterized [18]. It has also been shown that many popular all-atom force-fields yield a much higher melting point for long-chain alkanes than the experimental value, which in turn leads to drastically elevated density and viscosity values [16,17,19,20]. This may be critical in simulations of confined systems, where intricate phase transitions can heavily influence the tribological behavior observed [4,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…AA force-fields are much more computationally expensive and, as originally developed, many of them resulted in anomalous solid−liquid phase behaviour for the long-chain alkanes relevant to tribology [80]. Fortunately, the latter issue has been overcome by re-parameterising AA force-fields specifically for long-chain alkanes [8,9], which has led to far more accurate density and viscosity prediction (≈ 10% for n-hexadecane [10]), even under high temperature and high pressure (HTHP) conditions [10].…”
Section: Classical Force-fieldsmentioning
confidence: 99%
“…Fortunately, the latter issue has been overcome by re-parameterising AA force-fields specifically for long-chain alkanes [8,9], which has led to far more accurate density and viscosity prediction (≈ 10% for n-hexadecane [10]), even under high temperature and high pressure (HTHP) conditions [10]. More modest improvements in the density prediction of lubricantsized alkanes using AA force-fields can be made simply by reducing the intramolecular 1-4 scaling parameters for the L−J and electrostatic interactions using otherwise unmodified force-fields [80]. An increasing number of tribological NEMD studies are now employing accurate AA force-fields in order to yield more realistic viscous behaviour; however, for some types of molecules (multiple small branches, e.g., squalane) the additional computational expense compared to UA force-fields may not be justified.…”
Section: Classical Force-fieldsmentioning
confidence: 99%
“…15 For n-dodecane, we used a re-optimized OPLS All-Atom force field with scaling factor at 0.4. 18 The parameters for cross interactions between different molecular species (atomic groups) were derived using the standard Lorentz-Berthelot rules. 19 The particle−particle particle−mesh method, 20 as implemented in LAMMPS, 16 with a real space truncation distance of 15 Å and an accuracy of 10 -6 was used to treat the electrostatic interactions.…”
Section: Molecular Modelsmentioning
confidence: 99%